Textual signs (TS_III_XXVII) - Robinson, James M. (BrillOnline Reference Works, 2012)
A dot placed under a letter in the transcripton indicates that the letter is visually uncertain, even though the context may make the reading certain. Dots on the line outside of brackets in the transcription indicate missing letters that cannot be reconstructed but of which vestiges of ink remain